(untitled) - Steenkamp, Vanessa

Assessing the effects of two plants containing psychoactive compounds on the SH-SY5Y Parkinson’s disease neuroblastoma cell model (University of Pretoria, 2025)
Dissertation (MSc (Pharmacology))--University of Pretoria, 2024.